2000
DOI: 10.1079/095442200108729106
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic use in animal feed and its impact on human healt

Abstract: Antibiotic resistance in bacteria that cause disease in man is an issue of major concern. Although misuse of antibiotics in human medicine is the principal cause of the problem, antibiotic-resistant bacteria originating in animals are contributory factors, with some types of resistance in some species of bacteria. Antibiotics are added to animal feeds to treat and prevent infections and to improve growth and production. Until recently, the major concerns about incorporation of antibiotics in animal feeds relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
272
0
20

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 457 publications
(295 citation statements)
references
References 122 publications
3
272
0
20
Order By: Relevance
“…2A) than either the Danish or U.S. samples. The U.S. and Danish samples are similar, though the U.S. individuals have somewhat higher resistance potentials for macrolides, lincosamides, and streptogramins, common agricultural growth promoters (Barton 2000), as well as for cephalosporins, which are used prophylactically in food animals. The Danish antibiotic resistome, on the other hand, has a relative bias toward bacitracin and vancomycin and to a lesser extent toward streptomycin, spectomycin, and chloramphenicol.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…2A) than either the Danish or U.S. samples. The U.S. and Danish samples are similar, though the U.S. individuals have somewhat higher resistance potentials for macrolides, lincosamides, and streptogramins, common agricultural growth promoters (Barton 2000), as well as for cephalosporins, which are used prophylactically in food animals. The Danish antibiotic resistome, on the other hand, has a relative bias toward bacitracin and vancomycin and to a lesser extent toward streptomycin, spectomycin, and chloramphenicol.…”
Section: Resultsmentioning
confidence: 82%
“…The Danish antibiotic resistome, on the other hand, has a relative bias toward bacitracin and vancomycin and to a lesser extent toward streptomycin, spectomycin, and chloramphenicol. Notably, a vancomycin analog (avoparcin) has been previously administered to animals in Europe but not in the United States (Barton 2000), and was subsequently banned as its use was linked to a rapid European increase in vancomycinresistant enterococci (VRE) (Kjerulf et al 1996;Bager et al 1997;Barton 2000;Aarestrup 2012). The presence of VRE in Danish fecal samples has previously been linked to imported turkey meat (Agersø et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…However, colistin supplementation decreased villus height in the jejunum, which may be indicative for a reduction in absorption capacity (Pluske et al, 1997). This result is in contradiction with that of Barton (2000), who reported that chronic in-feed supplementation with antibiotics positively affects animal growth, due to a wide range of actions such as reducing the number of pathogens and bacterial toxins in the gut, a decreased nutrient use by bacteria and improving nutrient absorption. Other studies demonstrated that colistin supplementation in piglets infected by enterotoxigenic E. coli resulted in higher villus height compared with diets without antibiotics (Torrallardona et al, 2003;Wu et al, 2012).…”
mentioning
confidence: 73%
“…Se ha sugerido que el uso generalizado de agentes antimicrobianos, como las quinolonas en la ganadería para la producción de alimentos, ha contribuido con la emergencia y diseminación de aislamientos resistentes al ácido nalidíxico, los cuales pueden ser transmitidos a los humanos por vía de la cadena alimentaria (33). Aunque los aislamientos de Salmonella Enteritidis implicados en este brote y los identificados durante la vigilancia en años anteriores en Colombia, según puntos de corte de CLSI 2012 no presentan resistencia a ciprofloxacina, sí exhiben una CIM entre 0,125 y 1 µg/ml, considerada por algunos autores como disminución de la sensibilidad a las fluoroquinolonas (12,34).…”
Section: Caracterización Fenotípica Y Genotípica De Aislamientos De Punclassified